Interpreting the Findings From the Recent PCSK9 Monoclonal Antibody Cardiovascular Outcomes Trials - Wong, Nathan D.; Shapiro, Michael D. (Frontiers in Cardiovascular Medicine, 2019)
The recent development of monoclonal antibodies targeted to proprotein convertase subtilisin/kexin type 9 (PCSK9), e.g., PCSK9 inhibitors has revolutionized the landscape of lipid management. Many clinical trials assessing this class have demonstrated remarkable and consistent reductions in low-density lipoprotein-cholesterol. Moreover, the GLAGOV trial demonstrated the efficacy of evolocumab, when added to statin therapy, in reducing the progression of atherosclerosis measured by serial intravascular ultrasound, with the first suggestion of continued benefit down to LDL-C levels of 0.5 mmol/L (20 mg/dL). This trial was followed by the FOURIER Cardiovascular Outcomes trial in more than 27,000 patients with stable atherosclerotic cardiovascular disease (ASCVD) where evolocumab reduced the primary endpoint of atherosclerotic events by 15%, without significant safety differences between treatment groups. Furthermore, subgroup analyses suggested greater benefits seen in those with longer exposure to evolocumab recent acute coronary syndrome, multiple myocardial infarctions, multivessel coronary artery disease, peripheral arterial disease, as well as the subgroup who achieved very low low-density lipoprotein-cholesterol levels of below 0.3 mmol/L (10 mg/dL). Moreover, the EBBINGHAUS substudy demonstrated no differences in objectively measured cognitive function between treatment groups. The SPIRE 2 trial evaluating bococizumab in high-risk patients with baseline LDL-C ≥2.6 mmol/L (100 mg/dL) demonstrated significant atherosclerotic risk reduction, but the trial and further development of the drug was prematurely discontinued due to substantial attenuation of the LDL-C effect over time due to the development of neutralizing antibodies. Finally, the ODYSSEY Cardiovascular Outcomes trial testing alirocumab in subjects with recent (<1 year) acute coronary syndrome demonstrated a 15% relative risk reduction in the primary composite outcome, as well as a significant reduction in total mortality. Greater benefits were noted in those whose LDL-C at baseline was 2.6 mmol/L (100 mg/dL) or greater. These trials collectively demonstrate the added efficacy of PCSK9 inhibitors over moderate and high-intensity statin therapy for unprecedented low-density lipoprotein-cholesterol reduction and incremental ASCVD risk reduction.